Reliability Analysis of Power Distribution System - Ali, Khaidir; Wiyagi, Rama Okta; Syahputra, Ramadoni (Journal of Electrical Technology UMY, 2017)
Electrical distribution system is a component of electrical power system that is very important because it is closest to the customer. In its operation, the distribution system often suffers that causes the flow of electricity to the customer is interrupted. This situation is not expected by customers or by electric power companies. The more frequent and longer the occurrence of electrical power flow interruption, the lower the system reliability, and vice versa. Reliability of a distribution system can be analyzed based on SAIDI and SAIFI parameters. In this research, reliability analysis of distribution system on Gejayan substation. The analysis result using SAIDI and SAIFI parameters shows that Gejayan substation is reliable enough to national standard, while based on international standard still not reliable.